A review on catalytic oxidation of soot emitted from diesel fuelled engines. Issue 4 (August 2020) - Neha,; Prasad, Ram; Singh, Satya Vir
Abstract: In this review, the soot formation mechanism with an emphasis on their molecular structure is discussed, understanding of which is important to develop novel catalysts for soot oxidation. Further, a critical review of current catalytic soot oxidation scenario has been presented in this work. The various aspects affecting the activity of soot oxidation catalysts have been highlighted. The un-catalyzed and catalyzed (ceria based catalysts) kinetic soot oxidation models have also been examined. Recent advancements in catalyst design with a focus on the highly stable catalyst for soot oxidation have been given more emphasis considering their practical importance. A brief account of the notable work done on the exploration of novel soot oxidation catalysts via combinatorial catalysis is also being made.